1996
DOI: 10.2118/28994-pa
|View full text |Cite
|
Sign up to set email alerts
|

Deasphalted Oil: A Natural Asphaltene Solvent

Abstract: Summary Asphaltene deposition in the near-wellbore region can block pore throats, change wettability characteristics and relative-permeability relationships, and therefore, reduce oil production. Conventional aromatic solvents (e.g., toluene, xylene) alone or in combination with various dispersants are used to remove asphaltene damage from the near-wellbore region. However, these aromatic solvents are expensive and are not environmentally friendly. The objective of this work was to systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…The last studied sample was one asphaltene enriched in resins, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 solubility purposes. 57 A second interpretation, more alike to what was discussed in the preceding paragraphs, is provided by the works of Acevedo, Castillo and coworkers, 58,59 who showed that low solubility parameter asphaltenes fractions were found able to improve dissolution of "core asphaltenes" and modify their adsorptivity over solid surfaces. It is believed that low solubility parameter asphaltenes as described by …”
Section: Sample Viscosities As Evidence Of Cohesive Forcesmentioning
confidence: 87%
“…The last studied sample was one asphaltene enriched in resins, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 solubility purposes. 57 A second interpretation, more alike to what was discussed in the preceding paragraphs, is provided by the works of Acevedo, Castillo and coworkers, 58,59 who showed that low solubility parameter asphaltenes fractions were found able to improve dissolution of "core asphaltenes" and modify their adsorptivity over solid surfaces. It is believed that low solubility parameter asphaltenes as described by …”
Section: Sample Viscosities As Evidence Of Cohesive Forcesmentioning
confidence: 87%
“…Various laboratory techniques such as fluorescence spectroscopy, 10 conductive measurements, 11 acoustic resonance, 11,12 gravimetric, 13 and light-scattering technique (LST) [14][15][16][17] have been used in determining the onset of asphaltene precipitation conditions. A general summary of the various techniques can be found in Reference 18.…”
Section: Experimental Measurementsmentioning
confidence: 99%
“…Asphaltene problems have been treated mechanically, chemically, and/or operationally. Among available remedies in each technology that have been widely applied in the world (Jamaluddin et al 1996;Avila et al 2001;Kokal et al 2003;Wang and Civan 2005;Hamid 2006;Al-Ghazi and Lawson 2007;Frost et al 2008), the most conventional ways have been applied in our target fi eld. The selection of remedial action was based on operational and cost reasons.…”
Section: Introductionmentioning
confidence: 99%